Extracellular β-Glucosidase Production from bglp15.2 Gene Carrying Inulinase Signal Peptide in Saccharomyces cerevisiae BY4741 - Armaya Badiatul Fitri; Elvi Restiawaty; Maelita Ramdani Moeis (UIN Sunan Gunung Djati Bandung, 2017)
One of the important enzymes in cellulase complex is β-glucosidase. In this research, adding signal peptide of inulinase gene from Kluyveromyces marxianus, cloning, and expressing of bglp15.2 gene in S. cerevisiae BY4741 had been done. Gene of bglp15.2 encoding β-glucosidase has 90% identity to nucleotide sequence of Shewanella frigidimarina NCIMB 400 bacteria. Adding nucleotide sequence of signal peptide was aimed to secrete β-glucosidase and had been done with PCR (Polymerase Chain Reaction) method. The addition of nucleotide sequence of signal peptide in bglp15.2 gene had been done succesfully that indicated from nucleotide sequencing result and the increment of amplicon band size in electroferogram of the last addition PCR step. The bglp15.2 and bglp15.2INU gene (the bglp15.2 gene that has signal peptide nucleotide sequence) were cloned in Escherichia coli DH5α using pGEM-T-Easy vector and pBEVY-GL shuttle vector. The pBEVY-GL shuttle vector was used for transforming S. cerevisiae BY4741 with bglp15.2 and bglp15.2INU. The recombinant S. cerevisiae BY4741 carrying bglp15.2INU gene and growing in 48 hours had extracellularly β-glucosidase enzyme activity of 0,0178 U/ml and the intracellularly activity was 0,0181 U/ml. The β-glucosidase enzyme without signal peptide was not secreted. With K. marxianus inulinase signal peptide, about 50% Bglp15.2INU protein could be secreted. The protein molecular weight of secreted Bglp15.2INU was 44 kDa in SDS-PAGE result.